1999
DOI: 10.1093/brain/122.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

A pure case of Gerstmann syndrome with a subangular lesion

Abstract: The four symptoms composing Gerstmann's syndrome were postulated to result from a common cognitive denominator (Grundstörung) by Gerstmann himself. He suggested that it is a disorder of the body schema restricted to the hand and fingers. The existence of a Grundstörung has since been contested. Here we suggest that a common psychoneurological factor does exist, but should be related to transformations of mental images rather than to the body schema. A patient (H.P.) was studied, who presented the four symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
100
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(119 citation statements)
references
References 54 publications
13
100
0
2
Order By: Relevance
“…The lesions that cause acalculia of the Gerstmann's type are typically centred in the depth of the left intraparietal sulcus (Mayer, Martory, Pegna, Landis, Delavelle, & Annoni, 1999;Takayama, Sugishita, Akiguchi, & Kimura, 1994). This is compatible with the above brain-imaging results showing intraparietal activation during various numerical manipulation tasks independently of language.…”
Section: Neuropsychological Evidencesupporting
confidence: 87%
See 1 more Smart Citation
“…The lesions that cause acalculia of the Gerstmann's type are typically centred in the depth of the left intraparietal sulcus (Mayer, Martory, Pegna, Landis, Delavelle, & Annoni, 1999;Takayama, Sugishita, Akiguchi, & Kimura, 1994). This is compatible with the above brain-imaging results showing intraparietal activation during various numerical manipulation tasks independently of language.…”
Section: Neuropsychological Evidencesupporting
confidence: 87%
“…Inter-individual variability in the boundaries between cortical territories as well as in the branching patterns of this artery would explain that the different elements of Gerstmann's syndrome can be dissociated (Benton, 1961(Benton, , 1992. Note that this interpretation implies that, contrary to a frequent speculation, Gerstmann's syndrome does not result from a homogeneous impairment to a single representation that would somehow intermingle fingers, numbers, and space (Butterworth, 1999;Gerstmann, 1940;Mayer et al, 1999). Rather, the syndrome may represent a happenstance conjunction of distinct, but dissociable, deficits that frequently co-occur due to a common vascularisation, and that are only loosely connected at the functional level due to the overarching spatial and sensorimotor functions of the parietal lobe.…”
Section: Neuropsychological Evidencementioning
confidence: 98%
“…Traditionally, lateral posterior parietal cortex (including BAs 39, 40, and the posterior part of area 7) is thought to support planning and control of movement, as well as perception of, and attention to, spatial information (for influential models, see Corbetta & Shulman, 2002;Milner & Goodale, 1995;Mishkin, Ungerleider, & Macko, 1983;Nobre et al, 2001;Posner & Peterson, 1990), multisensory integration (Xing & Andersen, 2000) and construction (Critchley, 1953;Luria, 1973). For example, damage to posterior parietal cortex can limit awareness of the outside world, an object, or even of one's own body, so that only the contralesional half is consciously perceived (i.e., neglect; for theories, see Bisiach & Vallar, 1998;Dankert & Ferber, 2006;Driver & Vuilleumier, 2001;Karnath et al, 2001;Mayer et al, 1999;Rafal, 1997), and can impair the ability to detect multiple objects simultaneously (especially when they are in opposite hemifields; i.e., simultanagnosia; Balint, 1909Balint, /1995Rafal, 2002). Current models have proposed subdivisions of the posterior parietal region along functional lines.…”
Section: Lateral Region: Superior Parietal Lobule Angular Gyrus Andmentioning
confidence: 99%
“…These studies found that similar parietal networks (i.e., the angular gyrus) were activated when participants were submitted to tasks involving either finger movement control or number processing (Pesenti, Thioux, Seron, & De Volder, 2000;Piazza, Mechelli, Butterworth, & Price, 2002;Pinel, Piazza, Le Bihan, & Dehaene, 2004;Zago et al, 2001). Accordingly, the capacity to execute tasks requiring access to finger representations and numerical judgments was found to be disrupted after an acquired lesion (Gerstmann, 1930;Mayer et al, 1999) or a transient lesion (via repetitive transcranial magnetic stimulation [rTMS]) of the left angular gyrus (Rusconi, Walsh, & Butterworth, 2005).…”
mentioning
confidence: 99%